Prevalence of Stunting among Children Aged 6–23 Months in Kemba Woreda, Southern Ethiopia: A Community Based Cross-Sectional Study - Eskezyiaw Agedew; Tefera Chane (Advances in Public Health)
Background. Stunting is a public health problem in developing countries. Stunting (HAZ < −2 Z-score) is a major cause of disability preventing children who survive from reaching their full developmental potential. Objective. To assess stunting and associated factors among children aged 6–23 months in Southern Ethiopia. Methods. Community based cross-sectional study was carried out among 562 mothers who have children from 6 to 23 months in 2014/15 in Kemba district. Multivariate analyses were applied to identify predictor variables and control effect of confounding. Results. The study revealed that out of 562 children, 18.7% (95% CI (15.6–22.1)) of children were stunted. In multiple logistic regressions, boys [AOR: 2.50; 95% CI (1.60–4.01)], older mothers [AOR: 2.60; 95% CI (1.07–6.35)], mothers who have no formal education [AOR: 2.76; 95% CI (1.63–4.69)], mothers who work as daily workers [AOR: 3.06; 95% CI (1.03–9.12)] and have private work activity [AOR: 2.39; 95% CI (1.61–3.53)], mothers who have no postnatal follow-up [AOR: 1.64; 95% CI (1.05–2.55)], and maternal illness encountered after delivery [AOR: 1.56; 95% CI (1.05–2.32)] were identified as significant independent predictors of childhood stunting. Conclusion and Recommendation. A significant number of children had chronic undernutrition in critical periods. An organized effort should be made at all levels to solve the problems of chronic undernutrition (stunting) in children.